PELATIHAN BAHASA INGGRIS BAGI GENERASI MUDA PERUMAHAN GRIYA BATU AJI ASRI TAHAP 1,2 DAN 3 KELURAHAN SUNGAI LANGKAI KECAMATAN SAGULUNG - Evyanto, Winda; Johan, Mhd. (ASOSIASI IDEBAHASA KEPRI, 2025)
English training aimed at the younger generation at Griya Batu Aji Asri Housing Complex stages 1, 2, and 3 is a strategic effort in responding to the need for international communication skills that are increasingly important amidst global dynamics. This program is systematically designed with a technology-based approach and is tailored to the characteristics and needs of the participants. It is hoped that this training can encourage the formation of a young generation that is adaptive, competent, and ready to face global competition. In addition, this activity is also a means of empowerment, opening wider access to educational opportunities and the world of work, and contributing to creating a more advanced and competitive society.